2021
DOI: 10.1101/2021.10.19.21265187
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Symptoms compatible with long-COVID in healthcare workers with and without SARS-CoV-2 infection – results of a prospective multicenter cohort

Abstract: BackgroundThe burden of long-term symptoms (i.e. long-COVID) in patients after mild COVID-19 is debated. Within a cohort of healthcare workers (HCW), frequency and risk factors for symptoms compatible with long-COVID are assessed.MethodsParticipants answered baseline (August/September 2020) and weekly questionnaires on SARS-CoV-2 nasopharyngeal swab (NPS) results and acute disease symptoms. In January 2021, SARS-CoV-2 serology was performed; in March, symptoms compatible with long-COVID (including psychometric… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…Sex hormone differences in immune response [24] and autoimmunity triggered by SARS-CoV-2 have been suggested to be involved in the disease pathogenesis of long COVID [23]. Other studies have found that individuals with more symptoms during the acute phase were at a higher risk for developing long COVID [9, 14]. There are conflicting results regarding age in the risk for developing long COVID.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex hormone differences in immune response [24] and autoimmunity triggered by SARS-CoV-2 have been suggested to be involved in the disease pathogenesis of long COVID [23]. Other studies have found that individuals with more symptoms during the acute phase were at a higher risk for developing long COVID [9, 14]. There are conflicting results regarding age in the risk for developing long COVID.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we observed that non-confirmed COVID-19 cases reported similar residual symptoms after acute illness, albeit at a much lower frequency. Few studies have included a control group composed of symptomatic patients that tested negative for SARS-CoV-2 [14,30]. In a cohort of healthcare workers, olfactory disorders and hair loss were related to long COVID while positive and negative cases both had similar frequencies of 12/26 exhaustion/burnout and fatigue [14].…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that only initially symptomatic patients are at risk of long COVID. 22 Full calculations are detailed in Appendix 2.…”
Section: ‫ݕݐܾ݅݀݅ݎܯ‬ ൌ ‫݈݁ܿ݊݁ܽݒ݁ݎܲ‬ ൈ ‫݊݅ݐܽݎݑܦ‬ ൈ ‫ݕݐ݅ݎ݁ݒ݁ܵ‬mentioning
confidence: 99%
“…1 െ ሺ1 െ ‫ܹܦ‬ ሻ ൈ ሺ1 െ ‫ܹܦ‬ ሻ It was assumed that only initially symptomatic patients are at risk of long COVID 17 , and that calculations including all three-way (or higher) combinations of symptoms would make negligible difference.…”
Section: Morbidity Calculationsmentioning
confidence: 99%
“…Therefore, it is important to understand if physical activity can play a protective role on the ANS after SARS-CoV-2 infection. Antagonic effects of BMI and physical activity were observed in the management of neurocognitive and fatigue symptoms, and in the incidence of post-acute sequelae SARS-CoV-2 infection (PASC) in healthcare workers [31].…”
Section: Introductionmentioning
confidence: 99%